Salinity differently affects antioxidant content and amino acid profile in two cultivars of Amaranthus cruentus differing in salinity tolerance - Luyckx, Adrien; Beghin, Camille; QUINET, Muriel; ACHADE, Brice; PRODJINOTO, Hermann; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; LUTTS, Stanley (My University, 2021)
BACKGROUND: Amaranthus cruentus is a promising leafy vegetable with high nutritional value and is able to cope with salt stress but the impact of sodium chloride (NaCl) on its main properties have not been studied in detail. Plants from two contrasting cultivars (Rouge: salt-tolerant and Locale: salt-sensitive) were exposed to NaCl (0, 30, 60 and 90 mmol L–1 ) in nutrient solution for 2 weeks. Plant growth, mineral content, oxidative status and antioxidant concentration, salicylic acid concentration, protein content and amino acid profile were analyzed in the harvested leaves. RESULTS: Low dose (30 mmol L–1 NaCl) increased plant growth while Na+ accumulated to higher extent in salt-sensitive Locale than in salt-tolerant Rouge. A total of 30 mmol L–1 NaCl increased magnesium (Mg), phosphorus (P) and iron (Fe) content, as well as total antioxidant activity, ascorbate, phenolics, ⊍-tocopherol and carotenoids content to higher extent in cultivar (cv.) Rouge than in cv. Locale. Low (30 mmol L–1 ) and moderate salinities (60 mmol L–1 ) increased γ-tocopherol and total protein in cv. Locale. They also increased lysine, valine, methionine and proline concentration as well as chemical score of protein in this cultivar. The highest NaCl (90 mmol L–1 ) dose had a detrimental impact on both cultivars. CONCLUSIONS: It is concluded that A. cruentus is a promising plant species for saline agriculture since moderate doses of salt improve both quantitative and qualitative parameters in cultivar dependent manner.
Keywords: Amaranthus; antioxidant; NaCl; salinity; saline agriculture